Pengembangan Aplikasi Rekomendasi Musik Berdasarkan Lokasi Pada Platform Android - Komang Yoga Arimbawa; Ratih Kartika Dewi; Lutfi Fanani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Music is an important aspect within human daily life. The reason people listen to music is to fill spare time and to keep the mood in good condition. However, with so many music choices, users find it difficult to find music that suits their context. Examples such as considering music based on the location of the current user or the activity that is being carried out now. Required a system that can recommend music according to the context faced by the user. Application Development for Music Recommendations Based on Location moves on devices with the Android operating system. The recommendations are given in this system use the expert system method with forward chaining flow. The recommendation system will process the input obtained from the user and provide music recommendations in accordance with references provided by experts. Functional testing of this music recommendation system has met the requirements of "valid" by reaching a value of 100%. Similar to usability testing using the System Usability Scale method, this system managed to get a value of 75.5, this value is an indication that the system is in the acceptable category. This application can be used to find music according to the context considered based on the user's current location.